Health Education Using the FGD Method to Increase Pregnant Women's Knowledge About Nutrition in Pregnancy - Yuke Widyantari, Kadek; Yuliastuti Setioningsih, Fitri; Dita Hidayati, Rizka (Universitas Islam Lamongan, 2023)
Maternal nutrition during pregnancy plays an important role in the survival of the baby in the future. Planning nutrition programs for pregnant women is important because planning nutrition programs is known as an effort to deal with nutrition-related problems experienced by toddlers. The 2022 Indonesian Nutritional Status Survey (SSGI) provides an overview of the nutritional status of toddlers in Indonesia. SSGI reports that the prevalence of stunting in Indonesia is 24.4%, which will decrease to 21.6% in 2022. Inadequate nutritional intake during infancy and childhood, recurrent infections and inadequate psychosocial stimulation at the first thousand days of life, greatly contribute to stunted growth and development in children. This research is a type of quasi-experimental research with a one group pretest and posttest design involving one group of subjects. The sampling technique in this research was accidental sampling and a sample of 35 respondents was obtained. P value 0.000, these results indicate that providing health education interventions through the FGD method is significant in increasing pregnant women's knowledge regarding balanced nutrition in pregnant women. There is an influence between health education through the FGD method on increasing pregnant women's knowledge regarding balanced nutrition in pregnancy.